Safety, pharmacokinetics, and antitumour activity of trastuzumab deruxtecan (DS-8201), a HER2-targeting antibody–drug conjugate, in patients with advanced breast and gastric or gastro-oesophageal tumours: a phase 1 dose-escalation study. Issue 11 (November 2017) - Doi, Toshihiko; Shitara, Kohei; Naito, Yoichi; Shimomura, Akihiko; Fujiwara, Yasuhiro; Yonemori, Kan; Shimizu, Chikako; Shimoi, Tatsunori; Kuboki, Yasutoshi; Matsubara, Nobuaki; Kitano, Atsuko; Jikoh, Takahiro; et al.
Summary: Background: Antibody–drug conjugates have emerged as a powerful strategy in cancer therapy and combine the ability of monoclonal antibodies to specifically target tumour cells with the highly potent killing activity of drugs with payloads too toxic for systemic administration. Trastuzumab deruxtecan (also known as DS-8201) is an antibody–drug conjugate comprised of a humanised antibody against HER2, a novel enzyme-cleavable linker, and a topoisomerase I inhibitor payload. We assessed its safety and tolerability in patients with advanced breast and gastric or gastro-oesophageal tumours. Methods: This was an open-label, dose-escalation phase 1 trial done at two study sites in Japan. Eligible patients were at least 20 years old with breast or gastric or gastro-oesophageal carcinomas refractory to standard therapy regardless of HER2 status. Participants received initial intravenous doses of trastuzumab deruxtecan from 0·8 to 8·0 mg/kg and dose-limiting toxicities were assessed over a 21-day cycle; thereafter, dose reductions were implemented as needed and patients were treated once every 3 weeks until they had unacceptable toxic effects or their disease progressed. Primary endpoints included identification of safety and the maximum tolerated dose or recommended phase 2 dosing and were analysed in all participants who received at least one dose of study drug. The dose-escalation study is the first part of a two-part study with the second dose-expansion part ongoing and enrolling patients as of July 8, 2017, in Japan and the USA. This trial is registered atClinicalTrials.gov, numberNCT02564900 . Findings: Between Aug 28, 2015, and Aug 26, 2016, 24 patients were enrolled and received trastuzumab deruxtecan (n=3 for each of 0·8, 1·6, 3·2, and 8·0 mg/kg doses; n=6 for each of 5·4 and 6·4 mg/kg). Up to the study cutoff date of Feb 1, 2017, no dose-limiting toxic effects, substantial cardiovascular toxic effects, or deaths occurred. One patient was removed from the activity analysis because they had insufficient target lesions for analysis. The most common grade 3 adverse events were decreased lymphocyte (n=3) and decreased neutrophil count (n=2); and grade 4 anaemia was reported by one patient. Three serious adverse events—febrile neutropenia, intestinal perforation, and cholangitis—were reported by one patient each. Overall, in 23 evaluable patients, including six patients with low HER2-expressing tumours, ten patients achieved an objective response (43%, 95% CI 23·2–65·5). Disease control was achieved in 21 (91%; 95% CI 72·0–98·9) of 23 patients. Median follow-up time was 6·7 months (IQR 4·4–10·2), with nine (90%) of ten responses seen at doses of 5·4 mg/kg or greater. Interpretation: The maximum tolerated dose of trastuzumab deruxtecan was not reached. In this small, heavily pretreated study population, trastuzumab deruxtecan showed antitumour activity, even in low HER2-expressing tumours. Based on safety and activity, the most likely recommended phase 2 dosing is 5·4 or 6·4 mg/kg. Funding: Daiichi Sankyo Co, Ltd.